Commercially available rapid diagnostic tests for the detection of high priority pathogens: status and challenges. Issue 12 (1st June 2021) - Castillo-León, Jaime; Trebbien, Ramona; Castillo, John J.; Svendsen, Winnie E.
Abstract : Rapid diagnostic tests (RDTs) will provide a key element of disease surveillance. Their rapid turnaround, low cost, and accessibility in resource limited areas will help increase public health reporting and facilitate outbreak containment. Abstract : The ongoing COVID-19 pandemic has shown the importance of having analytical devices that allow a simple, fast, and robust detection of pathogens which cause epidemics and pandemics. The information these devices can collect is crucial for health authorities to make effective decisions to contain the disease's advance. The World Health Organization published a list of primary pathogens that have raised concern as potential causes of future pandemics. Unfortunately, there are no rapid diagnostic tests commercially available and approved by the regulatory bodies to detect most of the pathogens listed by the WHO. This report describes these pathogens, the available detection methods, and highlights areas where more attention is needed to produce rapid diagnostic tests for future pandemic surveillance.